2011
DOI: 10.1002/ejic.201101057
|View full text |Cite
|
Sign up to set email alerts
|

Thiolato‐Bridged Arene–Ruthenium Complexes: Synthesis, Molecular Structure, Reactivity, and Anticancer Activity of the Dinuclear Complexes [(arene)2Ru2(SR)2Cl2]

Abstract: Keywords: Ruthenium / Arene ligands / Thiolato bridges / CytotoxicityTreatment of an arene-ruthenium dichloride dimer with thiols RSH to lead to cationic trithiolato complexes of the type [(arene) 2 Ru 2 (SR) 3 ] + was shown to proceed through the neutral thiolato complexes [(arene) 2 Ru 2 (SR) 2 Cl 2 ], which have been isolated and characterized for arene = p-MeC 6 H 4 iPr and R = CH 2 Ph (1), CH 2 CH 2 Ph (2), CH 2 C 6 H 4 -p-tBu (3), and C 6 H 11 (4). The single-crystal X-ray structure analysis of the p-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 33 publications
11
46
0
Order By: Relevance
“…This does not appear to influence the SRu distances but slightly decreases the dative bond length to the aromatic ring (2.296 vs. 2.308 Å for the complexes), which may contribute to the stability of 2 a compared with 5 . Overall, the DFT calculation supports our findings and, considering the fact that complex 2 a is only obtained at low temperature and under strict stoichiometry,10 it is not surprising that complex 5 has remained undetected and that the formation of the metalla‐prisms were obtained from 2 .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This does not appear to influence the SRu distances but slightly decreases the dative bond length to the aromatic ring (2.296 vs. 2.308 Å for the complexes), which may contribute to the stability of 2 a compared with 5 . Overall, the DFT calculation supports our findings and, considering the fact that complex 2 a is only obtained at low temperature and under strict stoichiometry,10 it is not surprising that complex 5 has remained undetected and that the formation of the metalla‐prisms were obtained from 2 .…”
Section: Resultssupporting
confidence: 87%
“…Our first attempt involved use of the known chloro‐bridged metalla‐prism [( p ‐cymene) 6 Ru 6 Cl 6 (tpt) 2 ] 6+ as the starting material 11. In analogy to the preparation of the dithiolato‐bridged dinuclear arene ruthenium complexes 2 a – c , which involved addition of RSH to the dinuclear chloro‐bridged complex [( p ‐cymene) 2 Ru 2 Cl 4 ] at low temperature,10 an excess of RSH was added to [( p ‐cymene) 6 Ru 6 Cl 6 (tpt) 2 ](CF 3 SO 3 ) 6 in ethanol at 0 °C (Scheme S1). Unfortunately, only mixtures of compounds that we were unable to separate were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most active member of this family is [(η 6 ‐ p ‐Me‐C 6 H 4 i Pr) 2 Ru 2 (μ 2 ‐S‐ p ‐C 6 H 4 t Bu) 3 ]Cl, termed diruthenium‐1 or DiRu‐1 (Figure ) . This compound is very toxic in vitro toward hepatocellular carcinoma (HepG2 cells), estrogen‐responsive breast adenocarcinoma (MCF‐7 cells) and BT549 cells, triple‐negative breast adenocarcinoma (MDA‐MB‐231 cells), human ovarian cancer (A2780 cells), and the cisplatin‐resistant cell line A2780cis, with IC 50 values in the low nanomolar range . Recent in vivo studies, have demonstrated that these complexes have potential as anticancer drugs, especially DiRu‐1, which significantly prolongs the survival of tumor‐bearing mice .…”
Section: Introductionmentioning
confidence: 99%